AB0013 Some cytokines and bone markers in osteoarthritis. (1st June 2001) - Hulejova, H; Spacek, P; Adam, M
Abstract : Background: Osteoarthritis (OA) is a dynamic process involving joint as an organ and causing successive loss of structural integrity of different joint compartment constituents. OA is not a single disease entity but it is a group of overlapping disorders in which articular cartilage and subchondral bone are disturbed. Synovitis and formation of granulation tissue in subchondral bone take place in many patients with OA. Therefore at least some OA forms may be classified rather as inflammatory disease rather than degenerative disease. It is also a process where different biochemical factors besides mechanical take place. 1 Objectives: To elucidate the participation of some cytokines in OA pathological processes and to compare their values with those of bone markers. Methods: In sera of 32 OA patients in early as well as late stages with levels of Il-1b, Il-6, Il-8 and TNFa were established in Immulite (DPL, Los Angeles, CA, USA). Because serum levels of Il-1b and Il-6 were normal in all patients, in extracts from tissues obtained in TEP installation, only IL-8 and TNFa levels concentration were determined. Urinary pyridinoline (UPD) and deoxypyridinoline (UDPD) were determined with HPLC in the equipment of Spectra Physics (San Jose, CA, USA, type SP). 2 Chondrex (YKL-40) and bone alkaline phosphatase (BAP) were measured with ELISA test (Metra Biosystems, CA, USA). Values of Il-8 and TNFa don't correlate with Upyr and chondrex levels. Results: Concentration of cytokines in sera, synovial fluids and tissue extracts were increased only in some patients and mainly in synovial fluid. Markers of activity were increased in the both sera and tissue extracts. Conclusion: According to the results obtained Il-1b and Il-6 do not play any role in OA processes. On the other hand tissue concentrations of Il-8 and TNFa do not correlate with bone markers and therefore they not reflex activity of pathological process. References: Westacott CI, Sharif M. Cytokines in osteoarthritis: mediators or markers of joint destruction? Semin Arthritis Rheum. 1996;25(4): 254–72 paèek P, Hulejová H, Adam M. Ion exchange HPLC determination of pyridinium crosslinks in urine as markers of bone resorption. J Liq Chem Rel Technol. 1997;20(12):1921–30